2006
DOI: 10.3892/or.16.4.747
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression in normal-adenoma-carcinoma sequence suggests complex molecular carcinogenesis in colon

Abstract: Abstract. The majority of colon cancers develop from preexisting adenomas. We analyzed the expression profiles in the sequence of normal colon crypts, adenomas and earlystage carcinomas using microdissected cells from tubular adenomas with foci of malignant transformation. Differentially expressed genes were detected between normal-adenoma and adenoma-carcinoma, and were grouped according to the patterns of expression changes in the sequence. Down-regulated genes in the sequence included PLA2G2A, TSPAN1, PDCD4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
67
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 33 publications
10
67
0
1
Order By: Relevance
“…The ectopic expression of MTUS1 gene products has been shown to inhibit the cell proliferation [14,26]. The reduced expression of MTUS1 has been observed in colon cancer, ovarian cancer and pancreatic cancer [14,16,17]. These results, together with our study suggested that MTUS1 is a potential tumor suppressor gene for HNSCC and is a promising candidate for further functional analysis.…”
Section: Resultssupporting
confidence: 74%
“…The ectopic expression of MTUS1 gene products has been shown to inhibit the cell proliferation [14,26]. The reduced expression of MTUS1 has been observed in colon cancer, ovarian cancer and pancreatic cancer [14,16,17]. These results, together with our study suggested that MTUS1 is a potential tumor suppressor gene for HNSCC and is a promising candidate for further functional analysis.…”
Section: Resultssupporting
confidence: 74%
“…Reduced PDCD4 expression has been reported in at least six human tumor types or cancer cell lines (lung, brain, renal, breast, colon and pancreas) (Chen et al, 2003;Jansen et al, 2004;Ma et al, 2005;Lee et al, 2006), out of the nine solid tumors in which miR-21 is overexpressed (Chan et al, 2005;Iorio et al, 2005;Diederichs and Haber, 2006;Roldo et al, 2006;Volinia et al, 2006), indicating that mir-21/PDCD4 is likely to be a clinically significant oncogene:tumor suppressor pair in the induction and progression of human carcinomas.…”
Section: Mir-21 Targets Pdcd4 Z Lu Et Almentioning
confidence: 99%
“…Previously, the inhibitory effect of MTUS1 on cell proliferation was linked to the growth inhibitory signaling cascade by trans-inactivation of receptor tyrosine kinases in insulin, bFGF, PDGF and EGF-induced ERK2 activation (17). A previously published investigation demonstrated a significant down-regulation of MTUS1 in ovarian carcinoma tissues, implicating a possible role of MTUS1 on the development of ovarian carcinoma (18 (19)(20)(21). The gene responsible for tumor progression in colon cancer, located at chromosome 8p21.3-22 near marker D8S254, would be expected to be down-regulated in colon cancer (1,10).…”
Section: Introdutionmentioning
confidence: 99%